Zinc oxide influences intestinal integrity, the expressions of genes associated with inflammation and TLR4-myeloid differentiation factor 88 signaling pathways in weanling pigs. Issue 5 (July 2014) - Hu, Cai Hong; Song, Ze He; Xiao, Kan; Song, Juan; Jiao, Le Fei; Ke, Ya Lu
This study explored whether zinc oxide (ZnO) supplementation could alleviate weanling-induced intestinal injury through TLR and NOD-like receptor signaling pathways. Twelve early-weanling piglets were allotted to two dietary treatments (control vs 2200 mg Zn/kg from ZnO) for 1 wk. The results showed that supplemental ZnO improved daily gain and feed intake, decreased post weaning scour scores, increased villus height and villus height:crypt depth ratio at the jejunal mucosa, and decreased diamine oxidase activity and endotoxin concentration in plasma. The intestinal mRNA levels of TLR4 and its downstream signals, including MyD88, IL-1 receptor-associated kinase 1 and TNF-α receptor-associated factor 6, were decreased, and the expressions of intestinal pro-inflammatory cytokines and chemokines were decreased simultaneously in the ZnO-supplemented piglets. Although NF-κB p65 mRNA abundance was not affected by ZnO supplementation, NF-κB p65 protein expression was down-regulated by ZnO. However, ZnO supplementation had no effect on intestinal expressions of NOD1 and NOD2, and their adaptor molecule receptor-interacting serine/threonine-protein kinase 2, as well as protein expressions of caspase-3 and heat shock protein 70. The results indicated that the protective effects of ZnO on intestinal integrity were closely related to decreasing the expressions of genes associated with inflammation through inhibiting the TLR4-MyD88 signaling pathways.